2022
DOI: 10.3390/math10060902
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Conditional Density in Scalar-On-Function Regression Structure: k-N-N Local Linear Approach

Abstract: In this study, the problem of conditional density estimation of a scalar response variable, given a functional covariable, is considered. A new estimator is proposed by combining the k-nearest neighbors (k-N-N) procedure with the local linear approach. Then, the uniform consistency in the number of neighbors (UNN) of the proposed estimator is established. Such result is useful in the study of some data-driven rules. As a direct application and consequence of the conditional density estimation, we derive the UN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In Rachdi, Laksaci, Demongeot et al (2014), the leading term of the mean quadratic error of the LLE of the conditional density was then explicitly mentioned. Additionally, Zhou and Lin (2016) established the asymptotic normality of the LLE of the regression operator, and recently Almanjahie et al (2022) treated the k Nearest Neighbour kNN LLE of the conditional density in a scalar-On-Function regression structure, for additional research on the LLE in NFDA (Nonparametric Functional Data Analysis), see, Chahad et al (2017); Attouch et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Rachdi, Laksaci, Demongeot et al (2014), the leading term of the mean quadratic error of the LLE of the conditional density was then explicitly mentioned. Additionally, Zhou and Lin (2016) established the asymptotic normality of the LLE of the regression operator, and recently Almanjahie et al (2022) treated the k Nearest Neighbour kNN LLE of the conditional density in a scalar-On-Function regression structure, for additional research on the LLE in NFDA (Nonparametric Functional Data Analysis), see, Chahad et al (2017); Attouch et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such tools were extended to classification and discrimination analysis [4] discussed the application of several interesting statistical concepts to the functional data framework, including goodness-of-fit tests, portmanteau tests, and change point problems [5] was interested in analyzing variance for functional data, whereas [6] was more concerned with regression analysis for gaussian processes. Recent studies and surveys on functional data modeling and analysis can be found in [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introduction and Motivationsmentioning
confidence: 99%
“…The work in [5] focuses on analyzing variance for functional data, whereas that in [6] is more concerned with regression analysis for Gaussian processes. Recent studies and surveys on functional data modeling and analysis can be found in [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%